1997
DOI: 10.1159/000139474
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Central versus Parenteral Administration of Morphine Sulf ate on Regional Concentrations of Reduced Glutathione in Rat Brain

Abstract: Prior studies in rodents have shown significant depletion of reduced glutathione (GSH) in peripheral organs following acute systemic or central administration of opioids. However, little information exists on whether opioid administration affects concentrations of brain GSH. Recently, clinical observations have indicated acute declines of GSH concentrations in the cerebrospinal fluid of cancer patients after acute intracerebroventricular (ICV) morphine which may contribute to the development of organic behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…Vitamin E levels were decreased in our M and M + N groups and, as shown in Figure 1, negatively correlated with the levels of free MDA (Pearson's correlation coefficient r = −0.466; P = 0.005), thus further indicating the altered oxidative and antioxidative status of the rats in the M and M + N groups. The reduced antioxidant power in the rats treated with morphine or morphine + naloxone is in line with the findings of other authors, showing a decrease in reduced glutathione levels after morphine exposure, 12 or in antioxidant enzymes in mice treated with heroin 4,6 …”
Section: Discussionsupporting
confidence: 91%
“…Vitamin E levels were decreased in our M and M + N groups and, as shown in Figure 1, negatively correlated with the levels of free MDA (Pearson's correlation coefficient r = −0.466; P = 0.005), thus further indicating the altered oxidative and antioxidative status of the rats in the M and M + N groups. The reduced antioxidant power in the rats treated with morphine or morphine + naloxone is in line with the findings of other authors, showing a decrease in reduced glutathione levels after morphine exposure, 12 or in antioxidant enzymes in mice treated with heroin 4,6 …”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown significant depletion of GSH in peripheral organs following acute systemic or central administration of opioids. 9 The m-opioid receptor (MOR) the principal receptor involved in narcotic addiction, potentially play a key role in addiction, in combination with gene regulation and synaptic remodeling. 10 The MOR, which belongs to the family of seventransmembrane G-protein-coupled receptors, is a heavily N-glycosylated protein that regulates G proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown significant depletion of reduced glutathione (GSH) in peripheral organs following acute systemic or central administration of opioids [10]. One alternative to diminish the presence of endogenous free radicals induced by ageing and by the pathogenesis of many diseases requires the presence of glutathione (GSH) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, morphinedependent mice showed an increase in NO content in brain, which decreased by administration of melatonin, an important metabolite of serotonin (5-HT) [10]. 5-HT can capture free radicals present in damaged tissue [14], in addition to increasing oxidative metabolism by the presence of morphine [15].…”
Section: Introductionmentioning
confidence: 99%